Wound repair, safety, and functional outcomes in reconstructive lower extremity foot and ankle surgery using a dehydrated amnion/chorion allograft membrane. Issue 8 (3rd April 2022) - Tacktill, Jordan Z.; Rasor, Zachary; Adams, Josh; Driver, Gary; Shannon, Logan; Hudzinski, Scott; Carter, Marissa J.; Isaac, Adam L.; Zelen, Charles M.
Abstract: Amniotic membranes are known to be rich in growth factors, cytokines, and matrix proteins, which can help support wound closure and may improve patient outcomes in foot and ankle surgical interventions. In this Institutional Review Board (IRB) approved clinical study, 21 consecutive patients undergoing lower extremity soft tissue and bone reconstruction surgery received dehydrated human amnion and chorion allograft (dHACA) placed as a covering over the deep layers of the surgical wound during closure. Wound healing complications were assessed and American Orthopaedic Foot and Ankle Society (AOFAS) scores were compiled from over a 1‐year follow‐up period. Summary statistics were calculated for average pain, function, and alignment. The average overall AOFAS pre‐treatment score was 35.8 ± 23.0 and the post‐treatment score significantly improved to 87.5 ± 6.4 ( P = 3.7 × 10 −10 ). The pain‐score improved from pre‐treatment at 10.0 ± 11.0 to post‐treatment at 36.7 ± 4.8 ( P = 5.0 × 10 −5 ). The pre‐treatment function score was 18.7 ± 12.9 and at post‐treatment increased to 38.5 ± 5.7 ( P = 5.8 × 10 −5 ). Lastly, the alignment score at pre‐treatment was 7.1 ± 4.4 and at post‐treatment was 12.4 ± 2.6 ( P = .001). These improvements in functional scores were accompanied with clinical observations of reduced surgical complications including a lack of wound dehisance in the cohort. These clinical findings suggest that the application of aseptically processed dHACA may reduce wound complications and as such may aide in clinical improvements in foot and ankle surgical interventions however a larger comparative trial should be considered to validate these initial findings.